Serge Latouche e Michel Maffesoli tra filosofia ed ecologia - Dall'Igna, Antonio (Filosofia, 2015)
The present paper focuses on three cases in which philosophy universali- zes ecological concepts, with specific reference to the work of Serge Latouche and Michel Maffesoli. Firstly, both authors advocate a shift in the anthropocentric paradigm toward an ideal of humankind in harmony with nature. Latouche’s human being rules on the environment in respect of limits, while Maffesoli wishes for a neopagan return to an integral reality. Secondly, while Latouche’s suggestion for a degrowth was prompted by the concrete situation of the countries of the world’s South, Maffesoli makes the South the metaphysical pole of his neopagan and post-modern conception. Thirdly, for both authors the exceptionality of catastrophe is a key factor in reconfiguring the relationship between humankind and the world. While Latouche considers catastrophe as a way to bypass westernization, Maffesoli conceives of catastrophe as a turning point in the development of a panic and holistic reality.